TECHNICAL-ENERGY PERFORMANCE, OVERSIZING, AND SIMULTANEITY IN A RESIDENTIAL SOLAR POWER PLANT WITH ENPHASE MICROINVERTERS AND TRINA 705 W MODULES: A CASE STUDY IN FORTALEZA/CE - Mortol, Maicom Aparecido; Gomes, Rickardo Léo Ramos (Seven Editora, 2026)
Photovoltaic distributed generation has become established in Brazil as a relevant alternative for the energy transition, especially after the enactment of Law No. 14,300/2022, which redefined the rules of the Electric Energy Compensation System. In this context, it is important to evaluate not only the total energy generated by residential systems, but also the degree of simultaneity between generation and consumption, as well as sizing decisions (DC/AC ratio), which influence local energy use and the export of surplus energy. This study aims to analyze the technical-energy performance of a residential solar power plant with a decentralized architecture based on microinverters and high-power modules, installed in Fortaleza/CE, using real data at 15-minute intervals. The research is applied in nature, with a qualitative-quantitative approach and a case study procedure. Data from 10/19/2025 to 02/23/2026 were analyzed (generation, consumption, export, and import). The system consists of 12 Trina 705 Wp modules (8.46 kWp in direct current) and 12 Enphase IQ8P microinverters (5.7 kW in alternating current), with a DC/AC ratio of 1.48. The results indicated total generation of 5,444.03 kWh and a capacity factor of 31.34%, with occasional clipping during periods of higher irradiance (maximum observed power of 5.676 kW; 9.65% of intervals ≥ 5.6 kW). The estimated self-consumed energy was 579.11 kWh, resulting in a self-consumption rate of 10.64% and a self-sufficiency rate of 47.44%. It is concluded that the system presented consistent performance and that simultaneity is a central variable for interpreting energy utilization in residential settings, especially in projects with intentional surplus for compensation.